Interpretation Awareness of Creativity Mathematics Teacher High School - Mastuti, Ajeng Gelora; Nusantara, Toto; Purwanto; As'ari, Abdurrahman; Subanji; Abadyo; Susiswo (International education studies, 2016)
The purposes of this study are: a) to investigate high school math teacher creativity equality, b) to investigate what factors can inhibit their creativity consciousness. The subjects of this study consisted of two high school math teacher who had a different experience academically. The results of the qualitative research show the relationship between creativity and high school math teacher is focused on procedures and not on the product, presents the conception refers to the creativity in the perspective of learners. The observation of classes conducted by researchers for two weeks in a row can be used as an indicator that in teaching mathematics, high school teacher who observed indirectly applying creativity in teaching math though their confidence is lacking. They give an opportunity to him to be a creative individual and attractive in front of their students and provide opportunities to students to construct their own concepts and develop logical arguments. Overall a high school math teacher is still not directly aware of his creativity, but they can improve the confidence of the students. Based on the result of reflection and interviews obtained factors that can inhibit the creativity of teachers, among others; lack of confidence of teachers to students, the limited time to realize the ability of students, teachers internal and external activities that take a lot of time learning. Factors that could hinder the creativity of teachers compiled by researchers through depth interviews with high school teachers.